2018
DOI: 10.1371/journal.pone.0204032
|View full text |Cite
|
Sign up to set email alerts
|

Severity and properties of cardiac damage caused by Streptococcus pneumoniae are strain dependent

Abstract: Streptococcus pneumoniae is an opportunistic Gram-positive pathogen that can cause invasive disease. Recent studies have shown that S. pneumoniae is able to invade the myocardium and kill cardiomyocytes, with one-in-five adults hospitalized for pneumococcal pneumonia having a pneumonia-associated adverse cardiac event. Furthermore, clinical reports have shown up to a 10-year increased risk of adverse cardiac events in patients formerly hospitalized for pneumococcal bacteremia. In this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Viasus et al (141) derived a simple rule based on demographic and clinical features that was helpful in identifying patients with CAP at higher risk of acute cardiac events. With regard to bacterial factors of importance, the latter study indicated that those patients with pneumococcal pneumonia appeared to be at greater risk of CVEs and we have highlighted previously in this manuscript additional studies that have noted the importance of pneumococcal bacteremia, and/or infection with pneumococcal serotypes that cause high-grade bacteremia as being most important in respect of this pathogen (30,31). Other authors have suggested that patients with CAP due to Staphylococcus aureus and Klebsiella pneumoniae may also be at increased risk of CVEs (144).…”
Section: Treatment Of Capmentioning
confidence: 67%
See 1 more Smart Citation
“…Viasus et al (141) derived a simple rule based on demographic and clinical features that was helpful in identifying patients with CAP at higher risk of acute cardiac events. With regard to bacterial factors of importance, the latter study indicated that those patients with pneumococcal pneumonia appeared to be at greater risk of CVEs and we have highlighted previously in this manuscript additional studies that have noted the importance of pneumococcal bacteremia, and/or infection with pneumococcal serotypes that cause high-grade bacteremia as being most important in respect of this pathogen (30,31). Other authors have suggested that patients with CAP due to Staphylococcus aureus and Klebsiella pneumoniae may also be at increased risk of CVEs (144).…”
Section: Treatment Of Capmentioning
confidence: 67%
“…In their study, Shenoy et al using a murine model of invasive pneumococcal disease, demonstrated that cardiac damage only occurred in the setting of infection with those pneumococcal serotypes that caused high-grade bacteremia (31). Cardiac damage was assessed according to elevated serum cardiac troponin-I levels, as well as cardiac histology that varied according to pneumococcal serotype (31). These findings in the experimental setting confirm those of the clinical study reported by Borsa et al in patients with bacteremic and non-bacteremic pneumococcal pneumonia (30).…”
Section: Cardiac Complications In Pneumococcal Capmentioning
confidence: 99%
“…Although myocardial damage can also be induced by the systemic administration of recombinant PLY [70], a recent study has demonstrated that in the setting of severe, experimental pneumococcal infection caused by nine different serotypes of the pathogen, induction of cardiac damage is dependent on a high degree of bacteraemia and is also strain specific [71]. Importantly, the nine pneumococcal strains tested varied with respect to their levels of PLY expression, albeit in artificial culture medium in vitro, possibly consistent with serotyperelated, differential involvement of the toxin in the mediation of myocardial damage [71] and/or the ability of the pneumococcus to tightly regulate PLY production according to environmental conditions [72].…”
Section: Mechanism Referencesmentioning
confidence: 99%
“…Given that the pneumococcal serotype and extent of bacteraemia appear to be determinants of myocardial invasion, albeit in the setting of experimental disease , measurement of the magnitude of bacterial DNAemia, reported to be a putative marker of disease severity , may also identify those at highest risk of development of acute and even late‐onset CVEs.…”
Section: Biomarkers Of Myocardial Damagementioning
confidence: 99%
See 1 more Smart Citation